The mechanism of generating nanoporous Au by de-alloying amorphous alloys. (15th October 2016) - Paschalidou, E.M.; Celegato, F.; Scaglione, F.; Rizzi, P.; Battezzati, L.; Gebert, A.; Oswald, S.; Wolff, U.; Mihaylov, L.; Spassov, T.
Abstract: De-alloying, i.e. selective dissolution of alloys, is currently studied to produce nanoporous gold items suited for use in catalysis, electrochemical applications, sensors and actuators. Both crystalline and amorphous alloys can be selectively etched. In the former, less noble atoms are removed from surface terraces of grains layer by layer, while noble ones form mounds. These evolve by undercutting and electrolyte percolation to form a ligament network. The mechanism of ligament development by de-alloying amorphous alloys is unknown. Here we show that for de-alloying a Au-based glass, in this case Au40 Cu28 Ag7 Pd5 Si20, percolation of the electrolyte through cracks of the native surface oxide initiates the formation of protuberances which are soon undercut. An interlayer develops, where Au crystals germinate, grow to nanometer size by diffusion and impinge. This is how ligaments start to coarsen. The interlayer is found at all stages between coarsened ligaments and amorphous phase. The ligaments are defective polycrystals, as opposed to single crystals obtained from crystalline alloys. Graphical abstract: